2005
DOI: 10.1103/physrevlett.95.167002
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Geometrical Phase Transitions in Mesoscopic Superconductors by Scanning Tunneling Microscopy

Abstract: Using scanning tunneling microscopy, we mapped the distribution of the local density of states in a single crystal superconductor heterostructure with an array of submicron normal metal islands. We observe the coexistence of strongly interacting multiquanta vortex lattice with interstitial Abrikosov vortices. The newly formed composite magnetic flux structure undergoes a series of phase transitions between different topological configuration states. The vortex configuration states are strongly dependent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
96
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 14 publications
6
96
0
Order By: Relevance
“…In studies of vortex matter confined to narrow channels, the critical current or depinning force oscillates as a function of vortex density depending on how many rows of vortices can fit inside the channel [48,49]. More recent studies of twodimensional periodic pinning arrays show a dynamical commensuration effect that occurs in the limit where the vortices at the pinning sites remain pinned but the number of interstitial vortices flowing through interstitial regions increases with B/B φ [37].…”
Section: T R Cmentioning
confidence: 99%
“…In studies of vortex matter confined to narrow channels, the critical current or depinning force oscillates as a function of vortex density depending on how many rows of vortices can fit inside the channel [48,49]. More recent studies of twodimensional periodic pinning arrays show a dynamical commensuration effect that occurs in the limit where the vortices at the pinning sites remain pinned but the number of interstitial vortices flowing through interstitial regions increases with B/B φ [37].…”
Section: T R Cmentioning
confidence: 99%
“…STM measurements performed on magnetically coupled Permalloy(Py)/NbSe 2 (single crystal) bilayers 17 revealed that magnetic stripe domains induce vortex chain configurations that are quite different from the ones observed in superconductor/normal metal (S/N) hybrids 18 . At low fields vortices form chain structure spaced by d = 2w, where w is the magnetic stripe width of the Py domains.…”
mentioning
confidence: 96%
“…On the other hand, scanning tunneling microscopy (STM) 22 and Bitter decoration 23 imagings show an increase of the vorticity of the multi-quanta vortices in the hole after interstitial vortices were observed, revealing the effect of vortex-vortex interaction on the saturation number 16,19 . Though the pinning effect of a blind hole which allows the existence of multiple vortices of single flux quantum may be different from that of a normal (through-) hole having only one vortex with multi-quanta, its saturation number seems also to depend on the vortex-vortex interaction: an increase of vortex number in blind holes after the appearance of interstitial vortices was also proposed to understand the re-occurrence of peaks at high integer matching fields observed in critical current versus magnetic field curves for superconducting films with square arrays of blind holes 24 .…”
mentioning
confidence: 99%